2015
DOI: 10.1177/2049463715583142
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge, perceptions and attitudes to pain management among medical and nursing students: a review of the literature

Abstract: Introduction: Chronic pain results in significant personal, societal and economic burden. Doctors and nurses have a pivotal role in patient pain management. In order to determine the effectiveness of current pain education on knowledge, attitudes and perceptions of medical and nursing students, there needs to be a valid measure to assess and quantify these domains. We reviewed the literature to identify approaches for assessing knowledge, perceptions and attitudes to pain management among nursing and medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 52 publications
3
85
0
7
Order By: Relevance
“…Relieving children's pain has been perceived as a vital public health issue that needs immediate global attention since failing to manage pain can lead to economic and human burden on patients, their families, and society. [21,22] This study aimed to assess undergraduate nursing students' knowledge and attitude as regard pain management in children. The results revealed that more than half of nursing students' knowledge and attitudes about pain management was unsatisfactory as shown in Figure 1 and more than threequarters of undergraduate nursing students, their score response to PNKAS questions were less than 50% as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Relieving children's pain has been perceived as a vital public health issue that needs immediate global attention since failing to manage pain can lead to economic and human burden on patients, their families, and society. [21,22] This study aimed to assess undergraduate nursing students' knowledge and attitude as regard pain management in children. The results revealed that more than half of nursing students' knowledge and attitudes about pain management was unsatisfactory as shown in Figure 1 and more than threequarters of undergraduate nursing students, their score response to PNKAS questions were less than 50% as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…[2] In the United Kingdom 8% of the young population suffers from severe pain, [3] and in Australia 67% of the population aged 15 years or more complains of bodily pain. [4] The cost of responding to chronic pain was $34.3 billion in Australia in 2007, [5] and is a sum of between $560 and $635 billion annually in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The cost of responding to chronic pain was $34.3 billion in Australia in 2007, [5] and is a sum of between $560 and $635 billion annually in the United States. [2] Experiences of acute or/and chronic pain have detrimental physiological and psychological effects on one's life. [6][7][8] For example, children who experience chronic pain may complain of frequent school absenteeism and withdraw from social life.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] Much of the survey content was based on pain management standards of organizations such as the American Pain Society, the World Health Organization, and the Agency for Healthcare Research and Quality. [17][18][19][20][21][22][23][24][25] Much of the survey content was based on pain management standards of organizations such as the American Pain Society, the World Health Organization, and the Agency for Healthcare Research and Quality.…”
Section: Survey Developmentmentioning
confidence: 99%
“…The web-based survey was developed by the study investigators after a careful review of the literature. [17][18][19][20][21][22][23][24][25] Much of the survey content was based on pain management standards of organizations such as the American Pain Society, the World Health Organization, and the Agency for Healthcare Research and Quality. It was further reviewed by other clinicians who were considered content experts.…”
Section: Survey Developmentmentioning
confidence: 99%